Analysis of broiler chicken meat supply chain in Sukoharjo Regency, Central Java - Widadie, Fanny; Erlangga, Aditya Pramudya; Rahayu, Endang Siti (AGROMIX, 2025)
Introduction: The broiler chicken industry plays a vital role in fulfilling the animal protein needs of the people in Sukoharjo Regency, Central Java. Despite high production levels, challenges in the supply chain remain, particularly in pricing disparities between producers and consumers. The purpose of this study was to analyze the supply chain of broiler chicken meat in Sukoharjo Regency, Central Java. Methods: A descriptive analytical method was employed, utilizing both primary and secondary data. The analysis uses FSCN (Food Supply Chain Network) framework and performance metrics such as marketing margins and farmer’s share. Data were collected through interviews with 40 farmers and 12 supply chain institutions, supplemented by secondary data from local agencies. Results: Three supply chain channels were identified: Channel 1 (Farmers → Partner Companies → Brokers → Wholesalers → Retailers → Consumers), Channel 2 (Farmers → Partner Companies → Brokers → Wholesalers → Consumers), and Channel 3 (Farmers → Partner Companies → Brokers → Retailers → Consumers). Results showed that Channel 2 had the lowest total marketing margin (IDR 11,973/kg) and the highest farmer’s share (61.76%), indicating greater efficiency. Key challenges included price volatility, fragmented coordination, and limited government support. Conclusion: Based on farmer’s share and marketing margin analysis, channel 2 is the most efficient channel. The study recommends comprehensive upgrading strategies, including improving feed quality (product), adopting digital data management (process), and implementing livestock insurance (functional) to enhance supply chain resilience.